Papain Mediated Synthesized Gold Nanoparticles Encore the Potency of Bioconjugated Flutamide - Xu, Xiao; Man, Libo (Current Pharmaceutical Biotechnology, 2021)
Background: Prostate cancer is the second most common cause of male cancer death after lung cancer in the US. Therefore, there is an urgent need for a highly effective therapeutic drug at substantially low doses. Objective: Anti-androgen drug flutamide was delivered to the prostate cancer cells using Papain Mediated Synthesized Gold Nanoparticles (PGNPs) as the drug delivery system. PGNPs and flutamide worked synergistically against cancer cells. Methods: Flutamide was used to bioconjugate with PGNPs to improve its efficacy against prostate cancer. The synthesis and bioconjugation of flutamide with PGNPs (F-PGNPs) were characterized by various characterization techniques such as UV-vis spectroscopy, Transmission Electron Microscopy (TEM), Dynamic Light Scattering (DLS), and zeta potential to ensure the synthesis, size, shape, size distribution, and stability. The drug loading efficiency of flutamide in F-PGNPs was confirmed and validated by UV-vis spectroscopy. Eventually, in vitro studies were performed to determine the potency of F-PGNPs, changes in nuclear morphology, and generation of Reactive Oxygen Species (ROS). Results: The efficacy of F-PGNPs (IC50 is 46.54 μg/mL) was found to be improved significantly over pure flutamide (IC50 is 64.63 μg/mL) against human prostate cancer PC-3 cell line whereas F-PGNPs did not show any significant toxicity up to a fairly high concentration toward normal mouse macrophage J774A.1 cells. The apoptotic effects and ROS generation of F-PGNPs were analyzed by increased permeability of the cell membrane and condensed chromatin with deep blue and green fluorescent nucleus, respectively. Discussion: The results clearly showed that F-PGNPs significantly improved the potency of flutamide by delivering it directly into the nucleus of cancer cells through caveolae-dependent endocytosis. Conclusion: Thus, the greater inhibitory effect of F-PGNPs over the pure drug would be of great advantage during prostate cancer treatment.
Keywords: Flutamide